The Cornish-Fisher-Expansion in the context of Delta - Gamma - Normal approximations - Stefan R. Jaschke (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
Qualitative and quantitative properties of the Cornish-Fisher-Expansion in the context of Delta-Gamma-Normal approaches to the computation of Value at Risk are presented. Some qualitative deficiencies of the Cornish-Fisher-Expansion - the monotonicity of the distribution function as well as convergence are not guaranteed - make it seem unattractive. In many practical situations, however, its actual accuracy is more than sufficient and the Cornish-Fisher-approximation can be computed faster (and simpler) than other methods like numerical Fourier inversion. This paper tries to provide a balanced view on when and when not to use Cornish-Fisher in this context.
urn:nbn:de:kobv:11-10050077
Keywords: C10; 330; Value at Risk; Delta-Gamma-Normal; Cornish-Fisher expansion; Edgeworth series; Gram-Charlier series